1984
DOI: 10.1083/jcb.99.5.1696
|View full text |Cite
|
Sign up to set email alerts
|

Cell-substratum interaction of cultured avian osteoclasts is mediated by specific adhesion structures.

Abstract: The cell-substratum interaction was studied in cultures of osteoclasts isolated from the medullary bone of laying hens kept on low calcium diet. In fully spread osteoclasts, cellsubstratum adhesion mostly occurred within a continuous paramarginal area that corresponded also to the location of a thick network of intermediate filaments of the vimentin type. In this area, regular rows of short protrusions contacting the substratum and often forming a cup-shaped adhesion area were observed in the electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
190
0
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(206 citation statements)
references
References 37 publications
13
190
0
3
Order By: Relevance
“…They are formed by a F-actin core surrounded by a ring of scaffolding proteins such as vinculin, paxillin or talin. Interference-reflection microscopy indicated that the ring is in close proximity to the substratum suggesting that it mediates cell adhesive property (Marchisio et al, 1984). In agreement with that observation, integrins are localized at the ring and excluded from the core.…”
Section: Podosomes As Structural Units Of Osteoclast Adhesionssupporting
confidence: 82%
See 1 more Smart Citation
“…They are formed by a F-actin core surrounded by a ring of scaffolding proteins such as vinculin, paxillin or talin. Interference-reflection microscopy indicated that the ring is in close proximity to the substratum suggesting that it mediates cell adhesive property (Marchisio et al, 1984). In agreement with that observation, integrins are localized at the ring and excluded from the core.…”
Section: Podosomes As Structural Units Of Osteoclast Adhesionssupporting
confidence: 82%
“…Podosomes were then described as major adhesion structures found in monocytes and osteoclasts (Marchisio et al, 1984). They are formed by a F-actin core surrounded by a ring of scaffolding proteins such as vinculin, paxillin or talin.…”
Section: Podosomes As Structural Units Of Osteoclast Adhesionsmentioning
confidence: 99%
“…F-actin ring podosome belt formation is a prerequisite for OC bone resorption. 28,29 We used rhodamine-phalloidin staining to assess F-actin ring formation in primary OCs induced by M-CSF/RANKL from the bone marrow cells of the control and CD11b;Rgs12 fl/fl mice. About 60% of OCs from the control mice had complete and organized F-actin rings; whereas, only about 40% of OCs from CD11b;Rgs12 fl/fl mice had wellformed F-actin rings (Figures 5a and b, Po0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Podosomes are typically formed in cells of the monocytic lineage, such as macrophages (Lehto et al, 1982;Linder et al, 1999), osteoclasts (Marchisio et al, 1984) or (immature) dendritic cells (Burns et al, 2001). However, they can also be found or induced in a variety of other cell types, including smooth muscle cells (Gimona et al, 2003) and endothelial cells (Moreau et al, 2003;Osiak et al, 2005).…”
Section: Podosomes and Invadopodiamentioning
confidence: 99%